2016
DOI: 10.1108/ci-12-2015-0066
|View full text |Cite
|
Sign up to set email alerts
|

Reflecting on 10 years of focus on innovation, organisational learning and knowledge management literature in a construction project management context

Abstract: Purpose This paper provides a brief critical analysis of how the focus on innovation diffusion, organisational learning and knowledge management has developed with an emphasis on the 2005-2015 period. The purpose of this paper is to provide a recent historic perspective on these concepts and suggest an integrated future focus for this research. Design/methodology/approach The paper identifies trends in how knowledge and learning is associated with innovation and experience based on a literature review. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 44 publications
0
44
0
1
Order By: Relevance
“…Studies by Dossick and Neff (2010), Olatunji (2011), Merschbrock (2012, Walker (2016) and Mignone et al (2016) indicated that the organisational environment surrounding a BbCN, significantly affects collaboration in BbCNs. Alreshidi et al (2016) acknowledged this premise and termed such as impacts as "socio-organisational aspects".…”
Section: • Bim Educationmentioning
confidence: 99%
“…Studies by Dossick and Neff (2010), Olatunji (2011), Merschbrock (2012, Walker (2016) and Mignone et al (2016) indicated that the organisational environment surrounding a BbCN, significantly affects collaboration in BbCNs. Alreshidi et al (2016) acknowledged this premise and termed such as impacts as "socio-organisational aspects".…”
Section: • Bim Educationmentioning
confidence: 99%
“…For the purposes of this research, innovation is best defined as "an idea, practice or object that is new by an individual or other unit of adoption" (Rogers, 2003) as it is the 'newness' of the idea, which presents it as an innovation to a recipient (Lu and Sexton, 2007;Sexton and Barrett, 2003a). Receivers of innovation can range from individual entities such as a person or company to a wider population, such as an entire industry (Walker, 2016). Innovations create solutions to counteract problems and investment in innovation benefits customers and consumers through higher quality services (Staniewski et al, 2016).…”
Section: Innovation In Constructionmentioning
confidence: 99%
“…It has been further emphasized by Blanco et al (2018) recently regarding the adoption of applied AI in construction management in terms of project planning optimization, constructability justification, materials and inventory management, and risk and safety management; and these applications all demand a systems-based approach (Briesemeister, 2018) to improve the quality and productivity of construction management. It looks that an integrative use of data, information and knowledge (DIK) (Allee, 1997;Walker, 2016) is now just in front of the construction management profession, while the DIK set can be collected from either construction projects or construction professionals in dealing with specific issues such as those listed in Table 2 in a more accurate and efficient manner. In response to the increasing need for comprehensive use for DIK in construction management, a new concept about intelligent construction management system (iCMS) is described below in terms of its concept, purpose and value, conceptual model, and two tier systems.…”
Section: Intelligent Construction Management Systemmentioning
confidence: 99%